Effect of Na doping and heat treatment on the characteristics of ZnO thin films and ZnO/Si cells - Yesilkaya, S. Serkis; Alqader, Huda M. Abd (ELSEVIER, 2022)
Undoped and sodium doped ZnO thin films were grown on glass and Si substrates by spray pyrolysis. Post thermal annealing was applied for 1 h at 350 degrees C. Effect of Na doping and thermal annealing on the properties of ZnO thin films were investigated via XRD, UV-Visible spectrometry and resistivity measurements. Resistivity of the Na doped and annealed ZnO film was decreased to 7.15x10(3) Omega.cm from 3.26x10(4) Omega.cm where band gap energy was decreased to 3.31 eV from 3.36 eV. Current-voltage measurements held for all ZnO/Si heterostructures in dark and under illumination and device parameters were determined. Again best result obtained for the device in which both Na doping and annealing were applied as efficiency was increased to 4.57% from 2.01%.
Keywords: ZnO; Thin films; Na doping; Semiconductors; Heterojunctions; DOPED ZNO; AL; Materials Science; Physics